Los derechos fundamentales ante los avances de la tecnología - Ibarra Zavala, Brenda (UNIVERSIDAD DE SONORA, 2019)
The purpose of this paper is to evidence a problematic, as it is the asymmetrical shape in which new technologies of information and communication (NTIC'S) and the regulation of its use build up themselves and that neglect, makes vulnerable and unprotected fundamental rights. Contribution: Remarking the imminent need of reaching technology and legislation governing it. Certanly is true and urgent that the parliaments of the world propose and approve legislation on privacy, use of NTIC'S and human rights; true is also, which dealt with human rights, as members of a social conglomerate should not expect that all laws resolved it, but always seek justice, and for this purpose, it is necessary to appeal to the common sense of every human being, that can greatly help the effective protection of fundamental rights, for a better quality of life in society.